1998
DOI: 10.1115/1.2893840
|View full text |Cite
|
Sign up to set email alerts
|

A Vibrational Mode Analysis of Free Finite-Length Thick Cylinders Using the Finite Element Method

Abstract: Based on their three-dimensional mode shapes, the vibrational modes of free finite length thick cylinders can be classified into 6 categories, consisting of pure radial, radial motion with radial shearing, extensional, circumferential, axial bending, and global modes. This classification, together with the numbers of both the circumferential and the longitudinal nodes, is sufficient to identify each mode of a finite length thick cylinder. The mode classification was verified experimentally by measurements on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
2
12
0
Order By: Relevance
“…From Table 1, it is observed that a good agreement between the present calculated results and the results of literature [25] has been obtained.…”
Section: Comparison With Wang's Results [25] For a Non}rotating Cylinsupporting
confidence: 88%
See 4 more Smart Citations
“…From Table 1, it is observed that a good agreement between the present calculated results and the results of literature [25] has been obtained.…”
Section: Comparison With Wang's Results [25] For a Non}rotating Cylinsupporting
confidence: 88%
“…The boundary conditions are free at both ends ( Figure 1). The cylindrical shell has the following geometric properties and material properties, which are the same as that used in reference [25]. The only di!erence is that this is a rotating cylindrical shell now: l"0)254 m, r"0)09525 m, t"0)0381 m, E"2)07;10 N/m, "0)28, "7)86;10 kg/m.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations